2019
DOI: 10.1016/j.ijwd.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Nonmelanoma skin cancer in women

Abstract: Men continue to develop nonmelanoma skin cancer (NMSC) at higher rates than women, but the epidemiologic pattern of NMSC development is evolving. We present a selective, narrative review of the literature showing that there is a trend toward a development of basal cell carcinomas in women at younger ages, and highlight potential causes of this trend. We review evidence that indoor tanning is associated with the development of NMSC and show that young women use indoor tanning more than any other age-sex group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
(115 reference statements)
0
7
0
Order By: Relevance
“…From a behavioral perspective, indoor tanning, which is more prevalent in young women, is a possibility. 17,18 Results from a case-control study 19 have shown a significantly increased risk of early-onset (defined as age <40 years) BCC development in those who ever tanned compared with those who never tanned. Second, excess estrogen levels in women, which are especially pronounced in the premenopausal time frame, provide a biologically plausible mechanism for the increased BCC risk in young women that dissipates with age.…”
Section: Discussionmentioning
confidence: 99%
“…From a behavioral perspective, indoor tanning, which is more prevalent in young women, is a possibility. 17,18 Results from a case-control study 19 have shown a significantly increased risk of early-onset (defined as age <40 years) BCC development in those who ever tanned compared with those who never tanned. Second, excess estrogen levels in women, which are especially pronounced in the premenopausal time frame, provide a biologically plausible mechanism for the increased BCC risk in young women that dissipates with age.…”
Section: Discussionmentioning
confidence: 99%
“…However, indoor tanning, which uses artificially produced UV radiation, is more commonly used by women than men. In Europe, the incidence of KCs is increasing in both sexes; however, a faster increase in women than in men has been reported for BCCs ( 17 , 18 ). Sex-specific differences were recently observed with respect to lesion localization, i.e.…”
mentioning
confidence: 97%
“…This phenomenon is attributed to the use of tanning beds that became especially popular in women in the 1970s-1990s. 20,21,[23][24][25] Keeping the demographic development in mind, we can expect a constant increase of patients diagnosed with NMSC over the next years and decades.…”
Section: Seborrheic Keratoses 11mentioning
confidence: 99%